2010
DOI: 10.3109/15622975.2010.484466
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of repetitive transcranial magnetic stimulation on attention in ADHD Subjects: A randomized controlled pilot study

Abstract: Our findings should encourage future research on the possibility of amelioration of attention difficulties in patients suffering from ADHD by using high frequency rTMS directed to the right dorsolateral prefrontal cortex. (NIH registry NCT00825708).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 15 publications
0
46
0
3
Order By: Relevance
“…However, although TMS was successful in establishing an interference stimulation protocol that impaired cognitive control (Figner et al, 2010;Muggleton, Chen, Tzeng, Hung, & Juan, 2010), there are conflicting results as well. For example, the same repetitive stimulation protocol resulted in facilitative effects in several reported studies (Bloch et al, 2010;Cho et al, 2010). The inconsistent effects and other practical limitations of TMS, such as mobility and subjects' comfort, make it less than optimal for developing enhancement stimulation protocols.…”
Section: Effects Of Tdcs On Cognitive Controlmentioning
confidence: 96%
“…However, although TMS was successful in establishing an interference stimulation protocol that impaired cognitive control (Figner et al, 2010;Muggleton, Chen, Tzeng, Hung, & Juan, 2010), there are conflicting results as well. For example, the same repetitive stimulation protocol resulted in facilitative effects in several reported studies (Bloch et al, 2010;Cho et al, 2010). The inconsistent effects and other practical limitations of TMS, such as mobility and subjects' comfort, make it less than optimal for developing enhancement stimulation protocols.…”
Section: Effects Of Tdcs On Cognitive Controlmentioning
confidence: 96%
“…Dopaminergic activity in the prefrontal cortex is affected in ADHD, and rTMS affects dopaminergic secretion in the prefrontal cortex [43]. One small study has suggested promising results.…”
Section: Repetitive Transcranial Magnetic Stimulationmentioning
confidence: 98%
“…One small study has suggested promising results. Thirteen adults, who had ADHD diagnosed on DSM IV criteria, participated in a double-blind randomized crossover study that compared sham-brain stimulation and rTMS [43]. There was a specific beneficial effect on the patients' attention 10 min after a real rTMS course with no effect evident in the sham rTMS.…”
Section: Repetitive Transcranial Magnetic Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…One pilot single-session, sham-controlled trial found that high-frequency rTMS over the right DLPFC improved attention difficulties in ADHD patients (Bloch et al, 2010), although another study applying 10 consecutive sessions of high-frequency rTMS over the right DLPFC did not show significant differences in attention compared to sham rTMS (Weaver et al, 2012). It should be emphasized that not only the DLPFC but also other brain areas, such as the anterior cingulate cortex and the basal ganglia, are involved (Frodl & Skokauskas, 2012); nevertheless, for non-invasive brain stimulation purposes the DLPFC might be the most accessible gateway to modulate the cortico-subcortical pathways involved in ADHD.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%